Designing an Ethically-Oriented Management Model for Employee Education Development in Higher Education Using Grounded Theory (Case Study: Free Universities of Mazandaran Province) - Mohammadi Komroudi, Mohammad Javad; Ahmadi, Masoud; Farhadi Mahalli, Ali (Iranian Journal of Educational Sociology, 2022)
Purpose: One of the modern management approaches that has received significant attention and has addressed the weaknesses and problems of traditional management models is ethically-oriented management. Therefore, the purpose of this research is to design an ethically-oriented management model to enhance employee education in higher education, utilizing grounded theory in the free universities of Mazandaran province.Methodology: The nature of this study is exploratory and utilizes qualitative data. The research population consists of management experts and professors with management experience in the free universities of Mazandaran province. The researcher employed the snowball method to achieve theoretical saturation after conducting interviews with 13 experts and opinion leaders. Qualitative data were collected through structured interviews and analyzed using the qualitative method of grounded theory.Findings: Causal factors influencing ethically-oriented management for the development of employee education include personal characteristics, psychological capability, job identity, and organizational communications. Contextual factors include organizational ethics, organizational foundations, organizational justice, and leadership roles. Influential intervening factors include political, executive, infrastructural, and cultural factors. Additionally, three core phenomenon components have been identified and reported: ethical educational leadership skills, ethical literacy, and instructional design. Resulting strategies include external and internal university strategies, formal and informal strategies. Lastly, outcomes include structural development, educational development, communicational development, and performance development.Conclusion: This research began with the aim of achieving an ethically-oriented management model for the development of employee education in higher education using grounded theory and has completed its evolutionary journey through qualitative methods, resulting in a model. Finally, recommendations derived from the researcher's experiences are presented.